Examining the fraud awareness from the university’s academic staffs perspectives / Mohamad Ridhuan Mat Dangi and Noor Hasimah M. Yacob - Mat Dangi, Mohamad Ridhuan; M. Yacob, Noor Hasimah (Universiti Teknologi MARA Cawangan Pahang, 2013)
This study investigates the level of knowledge, awareness and understanding of fraud activities. It also identifies elements of fraud triangle theory which has the most influence on fraud activities and examines the fraudsters profile from academic staff perspectives. Findings from this study show that most of the academic staffs have a moderate knowledge and awareness of fraud and generally the information was obtained from the Internet. Most of them choose opportunity as the motivational factor for someone to perpetrate fraud and it will cause a serious problem to the society.